2021
DOI: 10.1088/1361-6463/ac13f6
|View full text |Cite
|
Sign up to set email alerts
|

Red afterglow and luminescence arising from defects in CaS:Eu2+, Tm3+

Abstract: CaS:Eu2+, Tm3+ is a phosphor known to emit a long afterglow of red emission (650 nm) when excited by blue light (450 nm). It shows a long afterglow time of 700 s for Eu = 0.05% and Tm = 2%. The mechanism of this afterglow is investigated using time-resolved fluorescence (TR-F) spectroscopy from the nanosecond to millisecond region. At room temperature, it is not possible to investigate shallow levels because of the effects of thermal vibrations. The mechanism of the emission characteristics at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Charge defects which were decreased by Na doping were suggested to serve as major trapping centers and to be responsible for the afterglow. In this study, small concentration of Eu0.1% is used, because PL efficiency and afterglow for Eu0.1% were found to be better than for Eu1% [16,32]. phosphors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Charge defects which were decreased by Na doping were suggested to serve as major trapping centers and to be responsible for the afterglow. In this study, small concentration of Eu0.1% is used, because PL efficiency and afterglow for Eu0.1% were found to be better than for Eu1% [16,32]. phosphors.…”
Section: Methodsmentioning
confidence: 99%
“…Timeresolved fluorescence spectroscopy and EPR study suggested that intrinsic S vacancies V S in the CaS host matrix are the probable reasons for the afterglow [32]. The trap levels located at 0.3 eV below the bottom of the conduction band of CaS cause the afterglow, and these trap levels are considered to be associated with V S [16,32]. The EPR signal of V S appears near 351 mT [32][33][34], and the data are plotted in figure 6.…”
Section: Psl In Cas:eu 2+mentioning
confidence: 99%
See 2 more Smart Citations
“…Alkaline-earth chalcogenides are indirect, wide band gap semiconductors of growing interest for optical applications . Doping them with rare earth ions results in luminescent phosphors suitable for bioimaging, , light-emitting diodes (LEDs), , thermal sensors, and photovoltaics . Among their different binary phases, alkaline-earth monochalcogenides, collectively referred to as AeCh or IIa-VIa semiconductors, are predicted to exhibit favorable thermoelectric properties in both their rock salt and hexagonal monolayer forms. , While these monochalcogenide phases traditionally adopt the rock salt structure, related polychalcogenide phases such as BaSe 2 and BaSe 3 adopt lower symmetry structures with distinct electronic properties (Figure ).…”
mentioning
confidence: 99%